(untitled) (Annals of Medical Research, 2022)
Aim: This study aims to evaluate the results of the patients with hepatoblastoma who underwent resection or liver transplantation. Material and Methods: The patients referred to our clinic for liver transplantation due to un-resectable hepatoblastoma were included in the study. They were evaluated according to demographic findings, alpha feto-protein level, the surgery type, and clinical results. Results: Between 2006 and 2020, 32 patients with hepatoblastoma were investigated among all liver transplant patients. All patients have been referred to us because of unresectable hepatoblastoma. Twenty-five patients underwent liver transplantation, and the other seven underwent hepatic resection without transplantation. The donor preparation has been done for all patients, including the resection group. The overall survival rate was 76% for transplant patients and 71.4% for resection patients. Conclusions: LT is an important surgical solution in patients with unresectable hepatoblastoma. In the state of requiring extended resection, preparing a donor simultaneously provides surgical options during the surgery.